TEMUAN STRUKTUR DI SITUS AIMOLI KABUPATEN ALOR, NUSA TENGGARA TIMUR - I Wayan Suantika (Forum Arkeologi, 2017)
The finding of structure in Aimoli, Alor is archaeologically important. This research aims to determine the form, function, role, and the cause of the structure damage. Methods that applied are excavation, survey, and interview. The data analysis consists of morphology analysis, technical analysis, style analysis, and comparative analysis. The finding of building components, namely pedestal stone, round and elliptical stone, etc. This structure is considered as part of sacred building. This structure experienced destruction that was caused by geographical condition, less quality material, and limited knowledge of technology.